Effects of SiO2 Incorporation on the Flexural Properties of a Denture Base Resin: An In Vitro Study - Alzayyat, Sara T.; Almutiri, Ghadah A.; Aljandan, Jawhara K.; Algarzai, Raneem M.; Khan, Soban Q.; Akhtar, Sultan; Ateeq, Ijlal Shahrukh; Gad, Mohammed M. (European Journal of Dentistry, 2021)
Objective The aim of this study was to evaluate the effects of the addition of low-silicon dioxide nanoparticles (nano-SiO2) on the flexural strength and elastic modulus of polymethyl methacrylate (PMMA) denture base material.Materials and Methods A total of 50 rectangular acrylic specimens (65 × 10 × 2.5 mm3) were fabricated from heat-polymerized acrylic resin. In accordance with the amount of nano-SiO2, specimens were divided into the following five groups (n = 10 per group): a control group with no added SiO2, and four test groups modified with 0.05, 0.25, 0.5, and 1.0 wt% nano-SiO2 of acrylic powder. Flexural strength and elastic modulus were measured by using a 3-point bending test with a universal testing machine. A scanning electron microscope was used for fracture surface analyses. Data analyses were conducted through analysis of variance and Tukey’s post hoc test (α = 0.05).Results Compared with the control group, flexural strength and modulus of elasticity tended to significantly increase (p ˂ 0.001) with the incorporation of nano-SiO2. In between the reinforced groups, the flexural strength significantly decreased (p ˂ 0.001) as the concentrations increased from 0.25 to 1.0%, with the 1.0% group showing the lowest value. Furthermore, the elastic modulus significantly increased (p ˂ 0.001) at 0.05% followed by 1.0%, 0.25%, 0.5%, and least in control group.Conclusion A low nano-SiO2 addition increased the flexural strength and elastic modulus of a PMMA denture base resin.
Keywords: denture base; elastic modulus; flexural strength; polymethyl methacrylate; silicon dioxide nanoparticles